2019
DOI: 10.1038/s41598-019-40158-9
|View full text |Cite
|
Sign up to set email alerts
|

Active propagation of dendritic electrical signals in C. elegans

Abstract: Active propagation of electrical signals in C . elegans neurons requires ion channels capable of regenerating membrane potentials. Here we report regenerative depolarization of a major gustatory sensory neuron, ASEL. Whole-cell patch-clamp recordings in vivo showed supralinear depolarization of ASEL upon current injection. Furthermore, stimulation of animal’s nose with NaCl evoked all-or-none membrane depolarization in ASEL. Mutant analysis s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 62 publications
(83 reference statements)
6
24
0
Order By: Relevance
“…elegans , Ca 2+ is thought to be the main charge carrier in membrane-potential changes, due to the lack of voltage-gated Na + channels in its neurons (Faumont et al., 2011, Faumont et al., 2006, Gao and Zhen, 2011, Goodman et al., 1998, Mellem et al., 2008, Shidara et al., 2013). Recently, the relationship between membrane potential and Ca 2+ channels has been thoroughly investigated, and it has been shown that Ca 2+ channels are necessary for membrane-potential spikes (Liu et al., 2018, Shindou et al., 2019). Ca 2+ responses in AIY regulate the animal's behavior (Li et al., 2014), so the results of information processing should be expressed as membrane-potential changes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…elegans , Ca 2+ is thought to be the main charge carrier in membrane-potential changes, due to the lack of voltage-gated Na + channels in its neurons (Faumont et al., 2011, Faumont et al., 2006, Gao and Zhen, 2011, Goodman et al., 1998, Mellem et al., 2008, Shidara et al., 2013). Recently, the relationship between membrane potential and Ca 2+ channels has been thoroughly investigated, and it has been shown that Ca 2+ channels are necessary for membrane-potential spikes (Liu et al., 2018, Shindou et al., 2019). Ca 2+ responses in AIY regulate the animal's behavior (Li et al., 2014), so the results of information processing should be expressed as membrane-potential changes.…”
Section: Resultsmentioning
confidence: 99%
“…This indicates that AIY neurons retain the function of Ca 2+ spike generation even without glutamate inputs. This suggests that the AIY neurons should have maintained their equilibrium potential even in the mutant animals because depolarization is necessary for generating Ca 2+ spikes (Liu et al., 2018, Shindou et al., 2019). In the mutants, glutamate inputs could not cause the depolarization of membrane potential beyond the threshold in response to environmental fluctuations by glutamate inputs, so the Ca 2+ spike frequency decreased.…”
Section: Discussionmentioning
confidence: 99%
“…These cGMP dynamics were observed specifically at sensory endings but not at soma, which was in contrast to Ca2+ dynamics that are uniform among subcompartments in AFD such as sensory ending, dendrite, soma and axon. Given that GCYs and TAX-2 and TAX-4 CNG channels localize at the sensory ending in AFD and that Ca2+ dynamics are uniform all over AFD, there is supposed to be a mechanism that propagates Ca2+ increase from the sensory endings (Shindou et al, 2019). We also found that the cGMP dynamics, which are supposed to be upstream of Ca2+ dynamics, reflected the comparison between past cultivation temperature and present ambient temperature, indicating that AFD memorizes temperature by simpler molecular mechanisms than so far expected from the results of Ca2+ imaging and membrane potential recording.…”
Section: Discussionmentioning
confidence: 99%
“…Being known as electrical synapses (Bennett 1997), gap junctions can synchronise electrical activities of the coupled neurons (Bennett and Zukin 2004). While neuronal and, to a lesser extent, sub-circuit functions have been extensively studied in C. elegans (Guo et al 2015;Larsch et al 2013;Liu et al 2018;Shindou et al 2019;Suzuki et al 2008), these have almost exclusively been limited to either the left or right side of the body, limiting our understanding of symmetry and asymmetry in sensory responses and information flow. With the exception of whole-brain imaging studies (Nguyen et al 2016;Schrödel et al 2013;Tobin et al 2002), imaging one or more pairs of bilateral neurons simultaneously has largely been avoided since, in most experiments, the animal lies on its left or right side, such that the two cells are not located in the same focal plane of the microscope (Chokshi et al 2010;Chronis et al 2007;Gordus et al 2015;Larsch et al 2015).…”
Section: Introductionmentioning
confidence: 99%